Use of excess meltwater from continuous flow analysis systems for the analysis of low concentration insoluble microparticles in ice cores - Tetzner, Dieter R.; Allen, Claire S.; Thomas, Elizabeth R.; Humby, Jack D. (Frontiers in Earth Science, 2025)
Low-concentration insoluble microparticles that are preserved in ice cores offer valuable information for reconstructing past environmental changes. However, their low concentrations and limited sample availability present challenges for extraction and recovery while ensuring representativeness of results. The analysis of ice cores using continuous flow analysis systems generates large volumes of excess meltwater as a by-product with the potential to improve the acquisition of targeted low-concentration insoluble microparticle samples. Here, we present Antarctic ice core diatom records, representative of targeted low-concentration insoluble microparticle records, recovered from excess meltwater generated from a continuous flow analysis system. We analyse these records to evaluate the feasibility of using this excess meltwater to generate replicable and representative results. Our results demonstrate that diatom records obtained from a continuous flow analysis system exhibit high recovery percentages and replicability, with minor quantifiable loss and memory effects in the system. Our multi-outlet sampling assessment highlights that the waste lines of the continuous flow analysis system are an optimal source for sampling excess meltwater. Additionally, the analysis of diatom spatial distribution in filters suggest a lower threshold for applying analytical methods which assume targeted microparticles are homogeneously distributed. These results confirm that a continuous flow analysis system can be used to extract targeted low-concentration insoluble microparticles from ice core samples, yielding representative and reproducible results.